The Effect of Endorphin Massage on Back Pain in Pregnant Women - Siska Anri Yani; Lidwina Trieleventa Lumruan Sihombing; Nadhiati Awlia Nasution (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
During pregnancy, the mother's body undergoes postural changes as a form of adjustment to the increase in the weight of the uterus. Back pain experienced by pregnant women can hinder daily activities and cause discomfort that affects the mother's physical and emotional condition. Therefore, back pain in pregnant women needs to be treated as early as possible so that the health of the mother and fetus is maintained during pregnancy. Endorphin massage is a form of therapy performed through gentle and calming massage, which is very beneficial for pregnant women. This study is a quasi-experimental quantitative research design, using a pretest-posttest one-group design to examine the effect of endorphin massage on back pain in pregnant women at the Putri Ayu Community Health Center in Jambi City. The average pain score before intervention was 6.00, indicating a fairly high level of pain. After the endorphin massage intervention, there was a significant change in pain distribution to 2.27. The results of the study indicate that endorphin massage has a significant effect on reducing the intensity of back pain in pregnant women in the working area of the Putri Ayu Community Health Center, with a significance value (p = 0.000).